(untitled) - Mattingly, Jack D. (New York, 1996)
This new text provides an introduction to the fundamentals of gas turbine engines and jet propulsion for aerospace or mechanical engineers. The book contains sufficient material for two sequential courses i propulsion (advanced fluid dynamics) an introductory course in jet propulsion and a gas turbine engine components course. The text is divided into four parts introduction to aircraft propulsion; basic concepts and one-dimensional/gas dynamics; analysis and performance of air breathing propulsion systems; and analysis and design of gas turbine engine components.
Keywords: Airplanes; Jet propulsion